2020
DOI: 10.21203/rs.3.rs-38143/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological Features and Hotspot of COVID-19 in Isfahan Province of Iran: Results of A Cohort Study

Abstract: Abstract Background and Aim: The aim of this study was to description of the epidemiological features and hotspot of COVID-19 in Isfahan province of Iran.Method: In this descriptive, retrospective cohort, multicenter study, all patients admitted to one of the hospitals or health networks of Isfahan province from 3rd February to 13th June 2020 due to RT-PCR (Reverse transcription-poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…demonstrated that in COVID-19 patients, ARDS is related to the level of troponin T. The increase in systolic pulmonary arterial pressures observed in all patients may be related to hypoxic vasoconstriction. [ 24 25 26 ] Likewise, in our study population, ARDS and acute cardiac injury were most common complications during hospitalization. Nonsurvivors were more likely to developed sepsis, ARDS acute cardiac injury, acute kidney injury, acute liver injury during hospitalization.…”
Section: Discussionmentioning
confidence: 78%
“…demonstrated that in COVID-19 patients, ARDS is related to the level of troponin T. The increase in systolic pulmonary arterial pressures observed in all patients may be related to hypoxic vasoconstriction. [ 24 25 26 ] Likewise, in our study population, ARDS and acute cardiac injury were most common complications during hospitalization. Nonsurvivors were more likely to developed sepsis, ARDS acute cardiac injury, acute kidney injury, acute liver injury during hospitalization.…”
Section: Discussionmentioning
confidence: 78%
“…The abovementioned results showed rheumatic patients with at least three months of hydroxychloroquine usage could benefit from the prophylactic effect of high tissue concentration of hydroxychloroquine. This study demonstrated the prophylactic effect of hydroxychloroquine by comparing the COVID-19 incidence rate in RA patients (4.2%) and the general population (approximately 27.5%) (14).…”
Section: Discussionmentioning
confidence: 79%
“…This proportion was even higher in rheumatic patients (31.6%) (13), while this study showed that only one in nine RA-patients required admission with no need to be intubated or ICU care. Furthermore, the mortality rate in the general population of Isfahan, Iran was 4.8% until June 2020 (14), while in these patients, no mortality was observed. Therefore, it seems that hydroxychloroquine has been able to reduce the possibility of infection and reduce the severity of the disease in patients who continuously administered hydroxychloroquine for several months and its blood level has reached a steady state.…”
Section: Discussionmentioning
confidence: 86%